SKRINING FITOKIMIA DAN UJI TOKSISITAS EKSTRAK DAUN BUAH HITAM (Haplolobus cf. Monticola Husson) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - AIsyah Ayu Indarsari; Evelina Somar; Sabir Sumarna (FMIPA Universitas Papua, 2023)
Indonesia is a country with the second highest terrestrial biodiversity wealth in the world. Some areas have endemic types of flora and fauna. One of the endemic flora found in Papua and widely found in Teluk Wondama district is piarawi or black fruit (Haplolobus cf. monticola Husson). The results showed that black fruit plants, both fruit and leaves, contain secondary metabolites that can cause pharmacological effects. The effectiveness of these active components as herbal medicines can be determined through a preliminary analysis in the form of a toxicity analysis. So far there has been no research on the content of secondary metabolites in the methanol extract of black fruit leaves. Thus, in this study, phytochemical and toxicity tests were carried out on the methanol extract of black fruit leaves (Haplolobus cf. monticola Husson) using the Brine Shrimp Lethality Test (BSLT) method. This test provides an overview of the toxicity level of black fruit leaf extract on Artemia salina Leach shrimp larvae. The test results can be used to identify bioative metabolites contained in black fruit leaves. Based on the results of the study, it can be concluded that the methanolic extract of black fruit leaves contains secondary metabolites such as alkaloids, flavonoids, saponins and tannins. Meanwhile, the results of the toxicity test showed that the LC50 value of the methanol extract of black fruit leaves was 102.5473779 ppm 102.53, so it could be categorized as moderately toxic.